Legal aspects of responsibility for publishing or re-publishing incorrect information on social media (a study in UAE law) - Ziad AL-Enizi; Ahmad Ghandour (Humanities & Social Sciences Communications)
Abstract This study outlines the legal aspects of the issue of responsibility for publishing or re-publishing misleading information on social media sites through four aspects: criminal liability, civil liability, identifying which court has jurisdiction over civil liability lawsuits, and applicable law to civil liability. The study concluded with the criminal and civil liability of the perpetrator of the act of publishing or republishing; the cases of jurisdiction of the Emirati court in civil liability claims; determining the law applicable to those cases, and other findings and recommendations, the most important of which were: the UAE Penal Code criminalizes this behavior and punishes it with a sentence of three to fifteen years imprisonment and a fine not exceeding one million dirhams. Regardless of the fairness of this punishment, no incident or court ruling is reported where the application of this punishment to the crime took place. Social media sites are known to be rife with misinformation and rumors, however, people who published or helped spread this information were not prosecuted, which may be due to the difficulty of tracking those who published this information or helped spread it technically. In this regard, the study recommends that relevant authorities develop their technical methods, such as the use of artificial intelligence in tracking the source of publishing that information and holding them accountable in accordance with the provisions of the law.